2020
DOI: 10.3390/antiox9080686
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Glucose-Related Protein 78 and 94 on Cisplatin-Mediated Ototoxicity

Abstract: Cisplatin is a widely used chemotherapeutic drug for treating various solid tumors. Ototoxicity is a major dose-limiting side effect of cisplatin, which causes progressive and irreversible sensorineural hearing loss. Here, we examined the protective effects of glucose-related protein (GRP) 78 and 94, also identified as endoplasmic reticulum (ER) chaperone proteins, on cisplatin-induced ototoxicity. Treating murine auditory cells (HEI-OC1) with 25 μM cisplatin for 24 h increased cell death resulting from excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Contrastingly, CHOP was upregulated after cisplatin exposure when Sal strongly decreased the expression. Notably, upregulation of BIP/GRP78 is protective against ischemic injury and also against cisplatin-induced damage in HEI-OC1 cells ( Ouyang et al, 2011 ; López-Hernández et al, 2015 ; Yi et al, 2020 ). Our results supported this point and further showed that pharmacological activation of eIF2α-BIP could alleviate cisplatin-induced ERS and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, CHOP was upregulated after cisplatin exposure when Sal strongly decreased the expression. Notably, upregulation of BIP/GRP78 is protective against ischemic injury and also against cisplatin-induced damage in HEI-OC1 cells ( Ouyang et al, 2011 ; López-Hernández et al, 2015 ; Yi et al, 2020 ). Our results supported this point and further showed that pharmacological activation of eIF2α-BIP could alleviate cisplatin-induced ERS and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study revealed that CoCl 2 pretreatment protected auditory hair cells (HEI-OC1) from H 2 O 2 -mediated cytotoxicity via the activation of the redox-sensitive transcription factors HIF-1α and NRF2, as well as their target gene PRDX6, indicating the protective roles of antioxidant enzymes against noise-triggered oxidative damage [136]. The involvement of oxidative stress in hearing impairment has also been reported in the case of cisplatin-mediated ototoxicity, where mild endoplasmic reticulum (ER)-related stress-induced upregulated expression of glucose-related protein (GRP) 78 and 94, resulting in the attenuation of intracellular ROS accumulation and cisplatin-triggered caspase-associated apoptotic signaling in HEI-OC1 cells [137], as shown in Figure 2.…”
Section: Hypoxic Preconditioningmentioning
confidence: 90%